Wallace, Dan oral history transcript - Wallace, Daniel (My University, 2009)
Transcript of an oral history with Dan Wallace, accelerator engineer, at the Synchrotron Radiation Center. Conducted by Eric Verbeten.
Keywords: Synchrotron, Wallace